2019
DOI: 10.1002/solr.201800286
|View full text |Cite
|
Sign up to set email alerts
|

Flexible ITO‐Free Organic Photovoltaics on Ultra‐Thin Flexible Glass Substrates with High Efficiency and Improved Stability

Abstract: The ability for organic solar cells to be conformable and bendable enables them to be used in a broad range of applications. Indium tin oxide (ITO) or PEDOT:PSS on plastic substrates such as poly(ethylene terephthalate) or poly(ethylene napthalate) (PET or PEN) have been used for transparent conductive electrodes (TCEs) for flexible devices. However, ITO is brittle and when used on flexible substrates is prone to cracking, and the acidity of PEDOT:PSS can lead to corrosion of the ester‐based plastic substrates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…However, some researchers found that the PEDOT:PSS with weak acidity may also lead to the device degradation during the storage. When the acid component PSS was removed to a certain extent by treating it with methanol or formic acid, the storage life time of the related device was effectively extended [147].…”
Section: Conducting Polymer Ftementioning
confidence: 99%
“…However, some researchers found that the PEDOT:PSS with weak acidity may also lead to the device degradation during the storage. When the acid component PSS was removed to a certain extent by treating it with methanol or formic acid, the storage life time of the related device was effectively extended [147].…”
Section: Conducting Polymer Ftementioning
confidence: 99%
“…Recently, Wang et al used flexible glass substrates (100 μm thick) to fabricate ITO-free OSC based on a BQR: PC 71 BM donor-acceptor system and achieved a PCE of 8% [351]. Nevertheless, Xiong et al has reported flexible OSC fabricated on an ITO coated PET substrate, using water processable PEIE as an ETL and PTB7-Th: IEICO-4F as the donor-acceptor system, demonstrating a high PCE of 12.5%.…”
Section: Flexible/ultra-thin Oscs For Wearable Electronicsmentioning
confidence: 99%
“…In a 2019 study, Wang et al [301] prepared TCEs based on high conductivity PEDOT:PSS PH 1000 on ultrathin (100 µm-thick) flexible glass substrates, with optimized TCEs exhibiting a R S of ≈30 Ω⋅□ −1 and a transmittance of ≈77% at 550 nm, with a broad transparency window observed between 300 and 800 nm. OPV cells with active area 1.6 cm 2 and with the structure glass/ PEDOT:PSS PH1000/MoOx/BQR:PC 71 BM/Ca/Al achieved a PCE of 5.2% (compared to 8.0% for devices with small area of 0.2 cm 2 ).…”
Section: Upscaling Using Conducting Polymer Transparent Conducting Electrodes As Bottom Electrodesmentioning
confidence: 99%